Expression of RANKL by dental cells during eruption of mice teeth - Jassim, Lubna K; Al- Hijazi, Athraa Y (Journal of Baghdad College of Dentistry, 2013)
Background : In order for a tooth to erupt, two obvious requirements are needed. First, there has to be alveolar bone resorption of the bone overlying the crown of the tooth such that an eruption pathway is formed. Second, resorption of bony crypt and apposition of new one, third, there has to be a biological process that will result in the tooth moving through this eruption pathway.The amniotic sac contains a considerable quantity of stem cells. These amniotic stem cells are multipotent and able to differentiate into various tissues, which may be useful for human application. Receptor activator of nuclear factor kappa B ligand (RANKL) is concentrated on bone biology, more specifically bone metabolism. RANKL plays a vital role in osteoclastogenesis for bone resorption. This study aimed to evaluate the expression of RANKL marker by dental cells during eruption of the teeth. Materials and Methods: : forty eight albino Swiss mice of one day old age injected with isolated amniotic stem cells in the anterior region of maxilla (incisors area) other 16 mice injected with saline represents control. Sacrifice 4 mice for each period (4, 7, 10, and 13) day old age. The result were studied histologically and immunohistochemistry. Results: The present results localized and identified RANKL marker in 3 areas of developing tooth of the studied groups includes overlying, surrounding and apical bone. Positive RANKL with high significant value expressed by osteoclast of overlying bone in Amnion group followed by Control at day 4. In surrounding bone positive expression of RANKL illustrated to be highest in Control followed by Amniotic fluid at day 10.Apical bone shows positive expression of RANKL in amniotic fluid group and it records to be the highest value in comparison to studied groups at day 10. Conclusion Expression marker RANKL illustrates that amniotic fluid group has a high expression of RANKL in osteoclast surrounding and apical bone areas while control expressed RANKL in osteoclast of overlying bone. The present results opened clinical hopes in dental tissue engineering by application of autologous amniotic fluid and chorion cells.